Seven new species of the earthworm genus Metaphire Sims & Easton, 1972 from Thailand (Clitellata: Megascolecidae) - Bantaowong, Ueangfa; Chanabun, Ratmanee; James, Samuel W.; Panha, Somsak (Zootaxa, 2016)
Earthworm specimens collected from various parts of Thailand were found to contain seven new species of the genus Metaphire Sims & Easton, 1972. These are M. songkhlaensis sp. n. in the octothecal pulauensis species group, M. trangensis sp. n. in the octothecal ignobilis species group, M. khaoluangensis sp. n. and M. khaochamao sp. n. in the sexthecal houlleti species group, M. doiphamon sp. n. in the sexthecal peguana species group, M. saxicalcis sp. n. in the quadrithecal planata species group, and the bithecal M. surinensis sp. n. Type material of some established species from Thailand or northern Malaysia was reinvestigated and illustrated to confirm the status of the new species and to facilitate species comparisons: M. pulauensis (Beddard, 1900), M. baruana (Stephenson, 1932), both with newly designated lectotypes, and M. planata (Gates, 1936), illustrated and redescribed.